2021
DOI: 10.1111/jfpe.13642
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mutton freshness grade discrimination based on hyperspectral imaging, near infrared spectroscopy and their fusion information

Abstract: The discrimination models of mutton freshness grades based on hyperspectral imaging (HSI, 400-1,000 nm), near infrared spectroscopy (NIRS, 900-2,500 nm) and their fusion information were established and compared in this study. Mutton freshness was divided into three grades by the comprehensive evaluation criterion. Then the characteristic variables were screened from preprocessed full-band variables, and discriminant models were established and compared based on the full-band variables, the characteristic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are some invalid or interfering information in the spectra, which can reduce the prediction accuracy of the model, and the amount of data contained in the spectra makes the running time of the model increase. Using the characteristic wavelength extraction algorithm to select the most representative characteristic wavelengths from the spectra can effectively improve the efficiency of the model operation 24–26 . In this study, the CARS algorithm was used to select the characteristic wavelengths.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some invalid or interfering information in the spectra, which can reduce the prediction accuracy of the model, and the amount of data contained in the spectra makes the running time of the model increase. Using the characteristic wavelength extraction algorithm to select the most representative characteristic wavelengths from the spectra can effectively improve the efficiency of the model operation 24–26 . In this study, the CARS algorithm was used to select the characteristic wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Using the characteristic wavelength extraction algorithm to select the most representative characteristic wavelengths from the spectra can effectively improve the efficiency of the model operation. [24][25][26] In this study, the CARS algorithm was used to select the characteristic wavelengths.…”
Section: Selection Of Characteristic Wavelengthmentioning
confidence: 99%
“…Extreme learning machine (ELM) (Bian, Li, Fan, Guo, & Chang, 2016) is a very popular machine learning algorithm, which used to train single hidden layer feedforward neural network (SLFN). This study used default function, default parameters, and the number of neurons in the hidden layer as 20 for training (Zhu et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental results demonstrated that the model achieved prediction accuracies of 0.91 and 0.94 for pork and chicken meat, respectively. Zhu et al [54] conducted a study on lamb freshness using hyperspectral imaging and near-infrared spectroscopy imaging. They collected freshness data for three different grades of lamb meat according to comprehensive evaluation standards for meat quality.…”
Section: Application Of Multi-source Information Fusion Technology On...mentioning
confidence: 99%